Experiences and challenges of Obo Manobo in Kidapawan City from their Mt. Apo ancestral domain to Ilomavis an ethnology of relocation - Villeza, Corinne V. (2022)
Independent of their goal, and regardless of whether they are begun by governments or private enterprises, large-scale development or infrastructure projects almost always necessitate the acquisition of land, often in extremely significant quantities. As a result of this requirement for land, people who live in the area may be forced to relocate ( i. e., physical displacement). It is with these kinds of development projects that create an impact on people?s livelihoods or income-generating activities, either temporarily or permanently (i.e., economic displacement), they could also have a negative impact on the environment and the social conditions needed for these people to live which would then make it impossible for them to live in their respective areas. In 1987, when the Philippines? Energy Development Corporation, or EDC, began planning a geothermal energy facility on Mount Apo, a dormant volcano on Mindanao?s southern island, it encountered fierce opposition. Although a lot of indigenous leaders fought for their land, they were given a promise development where everyone will have access to electricity and enjoy the benefits on the relocation sites such as food allowances, house, and even a better livelihood. Soon after, the EDC?s Geothermal Project of the EDC pushed through, relocation of the Obo Manobo community took place. Their struggles began anew as they attempted to adapt to their new surroundings, livelihood, and way of life. This paper is an ethnology of the Obo Manobo?s experience of displacement and relocation